2014
DOI: 10.1111/ajt.12694
|View full text |Cite
|
Sign up to set email alerts
|

BK Virus Encoded MicroRNAs Are Present in Blood of Renal Transplant Recipients With BK Viral Nephropathy

Abstract: BK viral infection is an important cause of renal transplant dysfunction and failure. Current strategies utilize surveillance for infection with DNA polymerase chain reaction assays and modulation of immunosuppression. Many viruses including polyomaviruses encode microRNAs (miRNAs). We have detected BK virus (BKV) encoded miRNAs in the blood of infected renal transplant recipients, and see a strong correlation between BKV encoded miRNA and BKV DNA in blood and a relationship between levels of bkv‐miR‐B1‐5p and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 26 publications
0
49
0
Order By: Relevance
“…Further, high rates of jcv-miR-J1-5p were found in plasma and urine samples of both JCV seropositive and, surprisingly, of seronegative individuals [37]. BKV miRNA has been detected in blood and urine samples of renal transplant recipients, and a correlation of microRNA expression and nephropathy was suggested [38,39].…”
Section: Discussionmentioning
confidence: 97%
“…Further, high rates of jcv-miR-J1-5p were found in plasma and urine samples of both JCV seropositive and, surprisingly, of seronegative individuals [37]. BKV miRNA has been detected in blood and urine samples of renal transplant recipients, and a correlation of microRNA expression and nephropathy was suggested [38,39].…”
Section: Discussionmentioning
confidence: 97%
“…In human Merkel cell carcinoma tumors, MCPyV miRNA 5p was expressed at low levels in 50% of MCPyV‐positive Merkel cell carcinomas . Several groups have examined polyomavirus miRNAs circulating in biological fluids obtained from subjects with different polyomaviruses DNA prevalence (Table ) . The first and second studies involved the same MS and HIV patients and healthy controls included in the study of the PBMC polyomavirus miRNA expression, reported above .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, BK virus microRNA can interfere with the production of ULBP3, which is recognized by NK cells, potentially helping BK virus–infected cells to evade the immune system 38. A strong correlation was found between BK virus–associated nephropathy (BKVAN) and the presence of BKV‐encoded microRNA in both blood and urine, but the study population was too small (31 BK‐positive patients compared to 15 controls) to determine whether BK microRNA detection has a higher predictive value than BK viral load for the diagnosis of BKVAN 36. The involvement of other virally encoded microRNAs in the pathophysiology of transplanted kidneys has not yet been elucidated.…”
Section: Virally Encoded Micrornas In Kidney Transplantationmentioning
confidence: 99%
“…Reactivation of BK virus is a frequent phenomenon after kidney transplantation, with BK virus copies identified in blood and urine of 30–50% of patients during the first year after transplantation 35. BK virus encodes a single precursor microRNA, bkv‐miR‐B1, which generates a mature ‐3p and ‐5p variant 36. These microRNAs have been demonstrated to target viral protein T antigen, thereby increasing DNA replication of the viral genome 37.…”
Section: Virally Encoded Micrornas In Kidney Transplantationmentioning
confidence: 99%